Establishing a carnivoran of extensive forests on an intensively managed landscape: Habitat and population establishment - Roger A. Powell; Aaron N. Facka; Deana L. Clifford; Kevin P. Smith; Sean M. Matthews; Ed Murphy; J. Scott Yaeger; Pete Figura; Richard Callas (PLoS ONE, 2025)
Reintroductions to establish populations usually occur in locations believed to have high-quality habitat to maximize the potential for high population growth rates and long-term population viability. Nonetheless, researchers and managers may have insufficient knowledge of what comprises high-quality habitat or of other requirements for members of a species with low population sizes or how to determine whether these conditions are present at potential reintroduction sites. Locations available for reintroduction may lack optimal habitat but have other characteristics that can benefit a reintroduction. Reintroductions allow rigorous study of reintroduced animals to improve understanding of a species’ biology and to inform future management and conservation actions. The fisher, a medium sized carnivoran in the family Mustelidae, is a long-lived (5–8 years) species of concern in western North America due, in part, to the perceived incompatibility of fishers and landscapes commercially managed for timber production. Due to concern about the status of fishers in California, from late 2009 to late 2011 we reintroduced 40 fishers from across northwestern California to the 648 km2, privately owned Stirling Management Area that was managed intensively for timber production in the northern Sierra Nevada and southern Cascades of California. The controlled initial conditions facilitated research into other aspects of fisher biology. We monitored reintroduced fishers and their offspring through 2017 to evaluate whether this managed landscape in California, predicted to possess adequate habitat for fishers, could support a new fisher population. Both female and male fishers had high monthly survival (>0.95). On average, 81% of adult females gave birth with a mean litter size of 1.9 ± 0.1 (minimum number of kits ±95% confidence interval). Survival and reproduction rates were constant across years and all vital rates were similar to most extant fisher populations elsewhere in California. By 2013, reproduction was effectively independent of the founding individuals. By 2017, the population was relatively small (n = 119 ± 96–141, 95% credible intervals) but had nearly tripled over the initial number reintroduced. Stochastic population simulations indicated that the population is unlikely to go extinct within the first 50 years after reintroduction, or 40 years after the completion of field research. Nevertheless, significant habitat changes resulting from wildfire could change those predictions. Thus, sites with landscape conditions similar to our study site and managed similarly for timber production should be considered when planning future fisher reintroductions.